PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA - yeni fristina (Jurnal Tunas Pendidikan, 2021)
The problem in this study is the student's learning achievement in mathematics learning in grade 1 SDN 04 / II Muara Bungo, this is evidenced by the results of preliminary observations made by researchers from 25 students, only 40% meet the KKM. The reason is that educators only use the lecture method which does not interest students to learn. The purpose of this study was to describe and determine the application of the demonstration method in improving mathematics learning achievement in Class 1. The type of research used in this study was classroom action research (CAR). This study consisted of two cycles, each cycle carried out through 4 stages, namely planning, acting, observing and reflecting and consisted of two meetings. The results of this study indicate that the average score has increased from 73 to 84 so that completeness reaches 90% of the students. 100% of all students are very active in the learning process. They try to quickly match the question cards and answer cards, so the efforts made by the author are good enough and this repair has stopped here.